Genetic assimilation in the evolution of hominin neuroplasticity - do Valle Miranda, Luiz (Studia Ecologiae et Bioethicae, 2019)
The discovery and popularisation of the study of different evolutionary processes outside the current evolutionary framework provide researchers of different areas with new tools to make progress in their field. In this work, I explored how genetic assimilation may have played a role in human evolution, more specifically the evolution of our brains. The results indicate that human brain evolution concerning neuroplasticity fits within a context of genetic assimilation. However, further studies in comparative genomics and neurogenetics are needed to fully understand how the evolutionary changes happened at the genetic level.